If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 4(-3x + 5) = 0 Reorder the terms: 2 + 4(5 + -3x) = 0 2 + (5 * 4 + -3x * 4) = 0 2 + (20 + -12x) = 0 Combine like terms: 2 + 20 = 22 22 + -12x = 0 Solving 22 + -12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + -12x = 0 + -22 Combine like terms: 22 + -22 = 0 0 + -12x = 0 + -22 -12x = 0 + -22 Combine like terms: 0 + -22 = -22 -12x = -22 Divide each side by '-12'. x = 1.833333333 Simplifying x = 1.833333333
| 5x+3(2x+18)=186 | | -21=19-8t | | 2x+6(2x-9)=16 | | d=250-6t | | 1.04g-6=0.76 | | -6-8(9+5m)= | | 4x-1=(2x+1)(x+2) | | -38-7x=18-9x | | 2x+3x+10=54 | | 13b+7=7 | | 12=7b-6-b | | (x+25)+(3x)+x=435 | | 5x-85=43-3x | | W+(-10)=18 | | 6t=4t | | V(x)=x(10-2x)(10-2x) | | 14-2c=18 | | 7.5m=-135 | | 1.4-2g=8.2 | | 19+.13m=.18m | | 10x=48+2x | | 3(4x+2)=21+5x | | 8(-3+4w)= | | 19wo+79=34cop | | (5w-4)w=57 | | -3x^2=-5x+8 | | 6-3v=12 | | 6(1-3p)-1=5(2p+1) | | x-64=24 | | 4(-5-2x)= | | 4(2x+8)=4x+8 | | 4.9t^2+1.5t-60=0 |